OCL: Modularising the Language - Akehurst, David; Zschaler, Steffen; Howells, Gareth (Electronic Communications of the EASST, 2007)
The Object Constraint Language (OCL) was originally designed as an `add-on' to the Unified Modelling Language (UML) in order to facilitate writing textual constraints complementing the graphical specifications. Since its original standardisation many extensions have been added to the language and many more have been proposed. The original structure of the OCL definition has not been formed, however, with a view of extensibility. Still, OCL can be redesigned in such a manner that it becomes easy to extend the language. In this paper we present a modular redefinition of OCL and illustrate how it supports extension. This new approach to the design of OCL enables you to consistently extend or customise OCL to your own needs.